A vinyl continent. Phonographic imaginaries of Latin America by the Italian label Vedette (1972–1978) (Revista Argentina de Musicología, 2026)
The Italian record industry of the 1970s, driven by the impact of the coup d’état in Chile in 1973, influenced the reshaping of Latin America’s image. Through its ‘phonographic diaspora’, the Nueva Canción Latinoamericana (New Latin American Song) and Andean music displaced the tropical stereotypes previously established by the American cultural industry, replacing them with an imaginary linked to social struggles and indigenous roots. This study focuses on the paraphonography (the set of iconography and texts accompanying the phonogram) of the Latin American discography published by Albatros and I dischi dello Zodiaco, both sub-labels of the Vedette publishing house. These labels not only distributed music by artists such as Inti-Illimani, Víctor Jara, Quilapayún, Pablo Milanés y Daniel Viglietti, among others, but also actively mediated culture, reinterpreting the original material and adapting it to the new context. The covers and paratexts functioned as pedagogical rather than commercial tools. In some cases, the aim was to extol the figure of the “committed singer”; in others, the visual design served to symbolise the social struggles of the continent. Furthermore, the inclusion ot ethnomusicological recordings in their catalogues reinforced the educational intention. Finally, this record production allowed Italian listeners to imagine a continent through a sound and visual map that combined artistic aesthetics with commitment.Editorial History:Received: January 23, 2026Accepted: April 29, 2026
Keywords: discography; transphonography; Nueva Canción Chilena; Andean music; folk revival